A sod-based cropping system for irrigation reductions. Issue 6 (20th October 2015) - Dourte, Daniel; Bartel, R.L.; George, S.; Marois, J.J.; Wright, D.L
Abstract: Cotton and peanut grown under irrigation make up over 769, 000 ha in the Southeast USA. The consumptive use of water for irrigation has significantly impacted groundwater resources, spring flows and streamflows in many parts of this region, particularly during severe droughts. This situation is further complicated with extreme weather events and climate variability. In this study, we compare yields and water use in a non-irrigated sod-based rotation system (SBR; bahiagrass–bahiagrass–peanut–cotton) to an irrigated conventional rotation system (ICR; peanut–cotton–cotton). Root mass of oat cover crop following peanut or cotton in a SBR and ICR system was also measured. A soil water assessment model (SWAT) was used to simulate irrigation water demands over a 34 yr period (1980–2013) under different soil types to quantify water saving potential of SBR. The average peanut yield in ICR from 2002 to 2013 was 4509 kg ha −1, while that in SBR was 4874 kg ha −1 . Likewise the average cotton yield in ICR during the same period was 1237 kg ha −1, while that in SBR was 1339 kg ha −1 . Oats had greater root mass in SBR than ICR. Simulation results indicate that crops in SBR consistently had substantially lower irrigation requirements (between 11 and 22 cm yr −1 ) than those in ICR in dry years. The water-saving potential of SBR varies positively with increasing sand content in soil.